2016
DOI: 10.12973/edupij.2016.51.2
|View full text |Cite
|
Sign up to set email alerts
|

Violence in Animated Feature Films: Implications for Children

Abstract: Cartoons and animated films occupy a significant proportion of a child's viewing time, but may be considered questionable in terms of their content. Although parents prefer such films in order to shield their children from daily problems and potentially harmful images in the media, examination of their content has so far been limited. In this study, violence depicted in popular animated cinema films was analyzed using content analysis, tabulating categories and frequency. Twenty-three animated films from among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…However, it is known that various pathologies occur due to the insensible, in other words excessive, use of these social media tools (Kuss & Griffiths, 2011). Studies have emphasized that individuals who spend their time online are lonelier in their real life (Shaw & Gant, 2002;Turkmen, 2016;Weiser, 2001). LaRose, Eastin, and Gregg (2001) define virtual environment as being alone in the crowd.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is known that various pathologies occur due to the insensible, in other words excessive, use of these social media tools (Kuss & Griffiths, 2011). Studies have emphasized that individuals who spend their time online are lonelier in their real life (Shaw & Gant, 2002;Turkmen, 2016;Weiser, 2001). LaRose, Eastin, and Gregg (2001) define virtual environment as being alone in the crowd.…”
Section: Introductionmentioning
confidence: 99%
“…The two objects of racial demonization in the animated film analyzed, Toshiaki and Nassor are boys. Male gender has also been shown as the dominant objects of negative portrayal in another study but regarding violent acts this time (Turkmen, 2016). These findings seem to suggest that males are key actors when it comes to negative occurrences in society or are perhaps deemed best 'models' for highlighting societal perceptions, misconceptions and prejudices due to the importance that patriarchy and traditional hyper masculinities force on them.…”
Section: Discussionmentioning
confidence: 81%
“…Qualitative research approaches such as semiotics let critical observers see demonization and stereotypes in every guise in creative works, empowering them to see beyond film aesthetics and ultimately become more media literate than ever before. For instance, according to Turkmen (2016), parents should watch these films with their children, and let them know that racial stereotypes in animated films are not always real-life representations; one animation film character is not enough to represent an entire race, and good and bad people cut across all races. The sort of empowerment made possible through semiotic analysis could lead to knowledge and understanding of demonization of 'people of colour' in films and other media texts, which in turn is an important starting point for censorship and advocacies against it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals feel lonely when their relationships with others are not at the desired levels and this feeling of loneliness makes them feel unhappy especially during their youth (Teppers, Luckyx, Klimstra, & Goossens, 2014). Studies have shown that loneliness is related to stress, social phobia, depression, shyness, and self-perception (Doane & Thurston, 2014;Ozen, 2016;Koenig & Abrams, 1999;Moore & Schultz, 1983, as cited in Karadas, 2014;Turkmen, 2016;Zhang et al, 2014). Individuals who generally experience loneliness also have low social relationship skills (Storch & Masia-Warner, 2004).…”
Section: Introductionmentioning
confidence: 99%